Collaborating internationally on physician leadership education: first steps. Issue 3 (4th July 2016) - Matlow, Anne; Chan, Ming-Ka; Bohnen, Jordan David; Blumenthal, Daniel Mark; Sánchez-Mendiola, Melchor; de Camps Meschino, Diane; Samson, Lindy Michelle; Busari, Jamiu
Abstract : Purpose: Physicians are often ill-equipped for the leadership activities their work demands. In part, this is due to a gap in traditional medical education. An emergent international network is developing a globally relevant leadership curriculum for postgraduate medical education. The purpose of this article is to share key learnings from this process to date. Design/methodology/approach: The Toronto International Summit on Leadership Education for Physicians (TISLEP) was hosted by the Royal College of Physicians and Surgeons of Canada, and the University of Toronto's Faculty of Medicine and Institute of Health Policy, Management and Evaluation. Of 64 attendees from eight countries, 34 joined working groups to develop leadership competencies. The CanMEDS Competency Framework, stage of learner development and venue of learning formed the scaffold for the work. Emotional intelligence was selected as the topic to test the feasibility of fruitful international collaboration; results were presented at TISLEP 2015. Findings: Dedicated international stakeholders engaged actively and constructively through defined working groups to develop a globally relevant, competency-based curriculum for physician leadership education. Eleven principles are recommended for consideration in physician leadership curriculum development. Defining common language and taxonomy is essential for a harmonized product. The importance of establishing an international network to support implementation, evaluation, sustainability and dissemination of the work was underscored. Originality/value: International stakeholders are collaborating successfully on a graduated, competency-based leadership curriculum for postgraduate medical learners. The final product will be available for adaptation to local needs. An international physician leadership education network is being developed to support and expand the work underway.